2019
DOI: 10.3389/fnhum.2019.00339
|View full text |Cite
|
Sign up to set email alerts
|

Adult Age Differences in the Use of Conceptual Combination as an Associative Encoding Strategy

Abstract: It is well-established that aging impairs memory for associations more than it does memory for single items. Aging also impacts processes involved in online language comprehension, including the ability to form integrated, message-level representations. These changes in comprehension processes could impact older adults’ associative memory performance, perhaps by reducing or altering the effectiveness of encoding strategies that encourage semantic integration. The present study examined age differences in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Visual half‐field studies have revealed that this effect is linked to right hemisphere‐biased processing (Huang et al., 2010). Like other forms of active comprehension, the concreteness effect is non‐obligatory, varying with stimulus type (Lee & Federmeier, 2008) and task demands related to imagery (Gullick et al., 2013), and, again, is reduced with normal aging (Huang et al., 2012; Lucas et al., 2017, 2019). Thus, both hemispheres augment basic comprehension with more active processes that, on the one hand (hemisphere!…”
Section: Active Comprehensionmentioning
confidence: 99%
“…Visual half‐field studies have revealed that this effect is linked to right hemisphere‐biased processing (Huang et al., 2010). Like other forms of active comprehension, the concreteness effect is non‐obligatory, varying with stimulus type (Lee & Federmeier, 2008) and task demands related to imagery (Gullick et al., 2013), and, again, is reduced with normal aging (Huang et al., 2012; Lucas et al., 2017, 2019). Thus, both hemispheres augment basic comprehension with more active processes that, on the one hand (hemisphere!…”
Section: Active Comprehensionmentioning
confidence: 99%
“…Moreover, effects of message‐level congruity on the N400 are delayed by over 200 ms in older adults (Federmeier et al, 2003). Ageing furthermore affects processing of compositional concreteness, that is, processing of the second noun in a noun–noun pair, in function of whether the first was concrete versus abstract (e.g., alias‐battle vs. skate‐battle) (Lucas et al, 2019), further suggesting that there are age‐related changes in compositional semantics in healthy older (compared with young) adults.…”
Section: Introductionmentioning
confidence: 99%
“…All were native Chinese speakers and had normal or corrected-to-normal visual acuity. They all were right-handed as measured via the Edinburgh Handedness Questionnaire and had a reliability of 0.87 in Chinese participants [ 59 ], which followed previous memory investigations [ 9 , 11 , 26 ]. None of them reported any history of neurological or psychiatric disorders and/or colour blindness.…”
Section: Methodsmentioning
confidence: 99%
“…In daily life, one may undergo numerous events, and some of them are bound together. Research on the memory of the combination of distinct events causes great attention, and such capability to remember events experienced together is referred to as associative memory [ 6 , 7 , 24 , 25 , 26 , 27 ]. In a typical associative recognition paradigm, several strings of pairs (e.g., A-B, C-D, and E-F) are studied, and in the following test, participants are instructed to determine whether a pair is intact (the same as the one in the preceding study phase, e.g., A-B), rearranged (both items in the pair are studied but are recombined, e.g., C-F), or new (both items are novel, e.g., G-H) [ 7 , 8 , 25 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%